2011
DOI: 10.1590/s0004-282x2011000500023
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic amyotrophic lateral sclerosis: new hypothesis regarding its etiology and pathogenesis suggests that astrocytes might be the primary target hosting a still unknown external agent

Abstract: This article briefly describes the already known clinical features and pathogenic mechanisms underlying sporadic amyotrophic lateral sclerosis, namely excitoxicity, oxidative stress, protein damage, inflammation, genetic abnormalities and neuronal death. Thereafter, it puts forward the hypothesis that astrocytes may be the cells which serve as targets for the harmful action of a still unknown environmental agent, while neuronal death may be a secondary event following the initial insult to glial cells. The art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Therefore, it becomes reasonable to assume that the astrocytes that influence a particular population of neurons devoted to a specific function constitute a singular population, only devoted to those types of cells 2,40 ; in this regard they should have their architecture and a metabolism particularly suited to the sustenance and control of those neurons' needs and activities.…”
Section: Astrocyte Domains and Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it becomes reasonable to assume that the astrocytes that influence a particular population of neurons devoted to a specific function constitute a singular population, only devoted to those types of cells 2,40 ; in this regard they should have their architecture and a metabolism particularly suited to the sustenance and control of those neurons' needs and activities.…”
Section: Astrocyte Domains and Subtypesmentioning
confidence: 99%
“…The physiological properties of astrocytes have been the subject of comprehensive reviews written in the last few years 1 , while other authors have highlighted the role that astrocytes play in the development of diseases previously attributed solely to neurons 2,3 .…”
mentioning
confidence: 99%
“…In a previous paper [1], we suggested that sporadic amyotrophic lateral sclerosis (SALS) was due to the action of a still unrecognised agent whose primary target would be the population of astrocytes related to motor neurons; this initial damage would start the sequence of pathological events in this illness, finally leading to death of the motor neurons. In addition, we proposed that the critical malfunction of the astrocytes was an inability to manufacture the EAAT2 (GTL-1) glutamate transporter [2,3]; more recent findings in patients and animal models now allow further consideration of this proposal.…”
Section: Introductionmentioning
confidence: 99%
“…In motor neuron disease linked to TAR DNA-binding protein 43 (TDP43), fused in sarcoma protein (FUS), ALS2 gene, VAPB gene, OPTN gene and C9ORF72 gene (chromosome 9 open reading frame 72) mechanisms 7,9 , few data regarding the involvement of glial cells are available, compared with cases related to SOD1 gene mutations.…”
Section: Primary Glial Cell Types and Functions Related To Motor Neurmentioning
confidence: 99%
“…effect) 7 . This review aims to summarize the most important data established on the role of glial cell types in ALS.…”
mentioning
confidence: 99%